2021
DOI: 10.1515/iral-2021-0138
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pragmalinguistic support on video-conferenced collaborative suggestion-giving task

Abstract: This study explored the impact of pragmalinguistic support on L2 users’ suggestion-giving task performance. Data came from 12 pairs of L2 users in a Zoom-mediated university course. They collaboratively wrote suggestions for improvement in their peers’ lesson plans using Office 365. Six pairs received pragmalinguistic support, while the others wrote their suggestions on their own. Audio-recorded pair discussions were coded qualitatively, and the written suggestions were analyzed in terms of linguistic and prag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The statement includes the idea that CL: “promotes learning and higher achievement of all the members as they share their resources and provide mutual support to each other.” In this context, Farzaneh and Nejadansari (2014) explain that “group setting facilitates creativity and learning of the members.” The participants of their study assigned a mean value of 3.85 to this item and considered it as the least preferred item among other variables. Jung and Fu (2021) reported that pragmalinguistic support helps enhance L2 learners’ understanding of the language and task content and enable them to generate lexically and pragmatically substantial output. The research of Johnson et al (1991) endorses that positive goal interdependence maximizes higher achievement and greater productivity than resource interdependence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statement includes the idea that CL: “promotes learning and higher achievement of all the members as they share their resources and provide mutual support to each other.” In this context, Farzaneh and Nejadansari (2014) explain that “group setting facilitates creativity and learning of the members.” The participants of their study assigned a mean value of 3.85 to this item and considered it as the least preferred item among other variables. Jung and Fu (2021) reported that pragmalinguistic support helps enhance L2 learners’ understanding of the language and task content and enable them to generate lexically and pragmatically substantial output. The research of Johnson et al (1991) endorses that positive goal interdependence maximizes higher achievement and greater productivity than resource interdependence.…”
Section: Resultsmentioning
confidence: 99%
“…The participants of their study assigned a mean value of 3.85 to this item and considered it as the least preferred item among other variables. Jung and Fu (2021) reported that pragmalinguistic support helps enhance L2 learners' understanding of the language and task content and enable them to generate lexically and pragmatically substantial output. The research of Johnson et al (1991) endorses that positive goal interdependence maximizes higher achievement and greater productivity than resource interdependence.…”
Section: Resultsmentioning
confidence: 99%